Journalism Meets Interaction Design: An Interdisciplinary Undergraduate Teaching Initiative. (March 2015) - Angus, Daniel; Doherty, Skye
As the media industry moves to a post-industrial model, there is a need for journalists—current and future—to have a deeper understanding of the ways that technology impacts their work and how best to produce journalism for mobile and networked devices. This article examines a teaching initiative designed to introduce journalism students to elements of social and mobile technology theory and design practice. Using feedback gained from peers, students, and industry professionals, the initiative was deemed successful; however, we outline several recommendations for improvement.